Advances in fertility-sparing surgery for cervical cancer. Issue 7 (July 2010) - Rob, Lukas; Pluta, Marek; Skapa, Petr; Robova, Helena
This article reviews the literature on fertility-sparing surgery in early cervical cancer. The article evaluates selection criteria, preoperative management and the most frequent surgical procedures used for preservation of fertility in cervical cancer. The article also analyzes oncological, fertility and pregnancy results. Oncological outcomes are not statistically different among single groups (vaginal radical trachelectomy, abdominal radical trachelectomy, simple trachelectomy or cone with or without neoadjuvant chemotherapy). Oncological results after fertility-sparing procedures in women with tumors smaller than 2 cm are comparable with women with the same risk factors after radical hysterectomy. Pregnancy following fertility-sparing surgery is associated with a variety of adverse pregnancy outcomes, especially second-trimester loss and preterm delivery. Less radical procedures (simple trachelectomy or cone with or without neoadjuvant chemotherapy) show statistically significant better pregnancy results. The pregnancy rate after abdominal radical trachelectomy was dramatically lower than in women treated with other types of fertility-sparing surgery. In the future, it will be necessary to optimize the technique and management of fertility-sparing surgery in order to attain good oncological results. Pregnancy outcomes should be given high priority. Fertility-sparing surgery is valuable for women who want to preserve their reproductive capability.